MENAFSIR YANG LEGAL, MENYEMPURNAKAN YANG MORAL - Donny Gahral Adian (Jurnal Hukum Progresif, 2009)
This article examines the problem of legal interpretation by critically analyzing the limitations of legal positivism and exploring Ronald Dworkin’s hermeneutic approach to adjudication. The study departs from the premise that legal texts are never entirely self-explanatory and that literal interpretation cannot adequately respond to the complexity of evolving social realities. Through a conceptual and philosophical analysis, the article contrasts H.L.A. Hart’s distinction between easy cases and hard cases with Dworkin’s theory of constructive interpretation. While Hart allows judicial discretion in hard cases, Dworkin argues that judges should remain bound to legal texts by uncovering the moral principles embedded within them rather than relying on subjective discretion. Legal interpretation, therefore, is understood as a constructive process that integrates legal rules, moral principles, and political ethics into a coherent judicial narrative. The article further demonstrates that adjudication is not merely the mechanical application of statutory provisions but an interpretive practice aimed at preserving the integrity of law. Nevertheless, it also identifies several philosophical limitations in Dworkin’s theory, particularly regarding the assumption that every legal text contains a discoverable original moral purpose and a coherent narrative unity. The article concludes that hermeneutic reasoning provides a more convincing framework than strict legal positivism for addressing contemporary legal disputes while simultaneously requiring critical reflection on the epistemological assumptions underlying legal interpretation.